Comprehensive gene assessment of estrogen receptor positive breast cancers reveals that HER2 positive status plays an important role in resistance to neoadjuvant letrozole - Webber, Victoria Louise (The University of Edinburgh, 2019)
Background The ER positive/ HER2 positive molecular subtype accounts for up to 10% of all breast cancers, these cancers have a worse prognosis than ER positive/ HER2 negative breast cancers. There is considerable evidence that ER positive/ HER2+ positive cancers exhibit resistance to endocrine therapy, yet it is unclear what is driving this resistance to therapy. The challenge is in identifying, early in the process of treatment decision making, who will respond to neoadjuvant letrozole therapy and who might benefit from the addition of combined HER2 targeted agents. Aims 1. To investigate which ER positive/ HER2 positive breast cancers respond to letrozole. 2. To compare the mechanisms of resistance to endocrine therapy in ER+/ HER2+ and ER+ / HER2- breast cancers. 3. To determine which cancers should be considered for combined endocrine and anti- HER2 treatment. Methods 17 postmenopausal women with large, operable, locally advanced ER positive/ HER2 positive breast cancers treated with neoadjuvant Letrozole had their clinical response assessed using periodic 3D ultrasound. Core biopsies were taken at 0, 14 days and 3 months of treatment. RNA was extracted, amplified, labelled and hybridised to Illumina HT-12 whole genome beadarrays. A group of patients with ER positive/ HER2 negative disease were identified to compare clinical and molecular response. Results 8 (47%) ER+/ HER2+ patients responded (R) and 9 (53%) patients did not (NR). HER2 expression was significantly higher at baseline in the NR group (p=0.005). Differences between R and NR and between the HER2+/ER+ and HER2-/ER+ groups were evident during treatment in terms of rate of change, magnitude of gene expression changes, and in change of functional molecular pathways. ER+/ HER2+ responding tumours had similar changes in gene expression over 3 months to ER+/ HER2- responding tumours. Analysis of responding tumours showed a clear association between good response and up regulation of stromal and immune response genes and down regulation of proliferation genes. In non responding tumours, mitogen activated protein kinase (MAPK) signalling and phosphoinositide 3-kinase (PI3K) signalling play important roles in resistance to neoadjuvant letrozole. Conclusions • ER+/ HER2+ and ER+/ HER2- responding tumours demonstrate similar gene changes in response to neoadjuvant letrozole, suggesting ER rather than HER2 is influencing growth in these cancers. • ER+/ HER2+ non responding tumours have fewer overall molecular changes on letrozole, maintaining high proliferation gene expression and active MAPK and PI3K signalling possibly suggesting HER2 signal transduction. • This may allow us to select ER+/ HER2+ tumours that will not benefit from endocrine therapy but may respond to HER2 or MAPK or PI3K targeted therapies.
Keywords: breast cancer; estrogen-receptor positive; ER positive; HER2; resistance; letrozole; endocrine therapy